2006
DOI: 10.1073/pnas.0508593103
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived cells fuse with normal and transformed intestinal stem cells

Abstract: intestine ͉ tumorigenesis ͉ cell fusion ͉ tissue regeneration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
224
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(246 citation statements)
references
References 33 publications
15
224
2
1
Order By: Relevance
“…Interestingly, stem or progenitor cells are suggested to be fusion partners of transplanted bone marrowderived cells in tissue regeneration, at least in the intestine 3 . Moreover, in Min mice, which have a mutation of adenomatous polyposis coli that leads to constitutive activation of Wnt / β -catenin signalling, the frequency of fusion with bone marrow-derived cells in the intestine is increased compared with the wild-type 3 . We hypothesize that the β -catenin / GCM1 / syncytin pathway-mediated cell fusion could be critical in some aspects of tissue regeneration and / or cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, stem or progenitor cells are suggested to be fusion partners of transplanted bone marrowderived cells in tissue regeneration, at least in the intestine 3 . Moreover, in Min mice, which have a mutation of adenomatous polyposis coli that leads to constitutive activation of Wnt / β -catenin signalling, the frequency of fusion with bone marrow-derived cells in the intestine is increased compared with the wild-type 3 . We hypothesize that the β -catenin / GCM1 / syncytin pathway-mediated cell fusion could be critical in some aspects of tissue regeneration and / or cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that cell fusion has a much broader role in tissue homeostasis and regeneration, such as in the fusion and transdiff erentiation of bone marrow-derived cells to neurons, hepatocytes, myocytes and epithelial cells in the intestine 1,3 . Advances in the study of cell fusion in tissue repair and regeneration, particularly in infl ammatory conditions, have prompted the revival of an earlier theory, which postulates that cell fusion is one of the driving forces of cancer initiation and progression.…”
mentioning
confidence: 99%
“…Conceptually, cell fusion between stem cells and mutated cells might lead to regaining of self-renewal capacity to allow further accumulation of transforming mutations. A recent study has shown that BMDCs were able to fuse to neoplastic epithelium [54]. Additionally, the fusogenic factor CD44 is used as a positive surface marker for CSCs in breast cancer…”
Section: Origins Of Cscsmentioning
confidence: 99%
“…
AbstractTransplanted bone marrow derived cells (BMDCs) have been reported to fuse with cells of diverse tissues [1][2][3][4][5][6][7][8][9][10][11][12][13] , but the extremely low frequency of fusion has led to the view that such events are biologically insignificant. Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects.
…”
mentioning
confidence: 99%
“…cells of a number of tissues including skeletal muscle, liver, intestine, and brain 1,3,4,[8][9][10][11][12] . However, the low incidence of fusion, which increases somewhat with tissue damage 2,4,18 , has raised questions regarding its significance 19 .…”
mentioning
confidence: 99%